Alterations in Urine Metabolomics Following Sport-Related Concussion: A 1H NMR-Based Analysis - Wanner, Zachary R.; Southam, Cormac G.; Sanghavi, Prachi; Boora, Naveenjyote S.; Paxman, Eric J.; Dukelow, Sean P.; Benson, Brian W.; Montina, Tony; Metz, Gerlinde A. S.; Debert, Chantel T. (Frontiers in Neurology, 2021)
Objective: Millions of sport-related concussions (SRC) occur annually in North America, and current diagnosis of concussion is based largely on subjective clinical evaluations. The objective of this study was to determine whether urinary metabolites are significantly altered post-SRC compared to pre-injury. Setting: Outpatient Sports Medicine Clinic Participants: Twenty-six male youth sport participants Methods: Urine was analyzed pre-injury and after SRC by 1H NMR spectroscopy. Data was analyzed using multivariate statistics, pairwise t-test, and metabolic pathway analysis. Variable Importance Analysis based on random Variable Combination (VIAVC) was applied to the entire data set and resulted in a panel of 18 features. Partial Least Squares Discriminant Analysis was performed exploring the separation between pre-injury and post-SRC groups. Pathway topography analysis was completed to identify biological pathway involvement. Spearman correlations provide support for the relationships between symptom burden and length of return to play and quantifiable metabolic changes in the human urinary metabolome. Results: Phenylalanine and 3-indoxysulfate were upregulated, while citrate, propylene glycol, 1-methylhistidine, 3-methylhistidine, anserine, and carnosine were downregulated following SRC. A Receiver Operator Curve (ROC) tool constructed using the 18-feature classifier had an Area Under the Curve (AUC) of 0.887. A pairwise t-test found an additional 19 altered features, 7 of which overlapped with the VIAVC analysis. Pathway topology analysis indicated that Aminoacyl-tRNA biosynthesis and beta-alanine metabolism were the two pathways most significantly changed. There was a significant positive correlation between post-SRC 2-hydroxybutyrate and the length of return to play ( = 0.482, p = 0.02) as well as the number of symptoms and post-SRC lactose ( = 0.422, p = 0.036). Conclusion: We found 1H NMR metabolomic urinary analysis can identify a set of metabolites that can correctly classify SRC with an accuracy of 81.6%, suggesting potential for a more objective method of characterizing SRC. Correlations to both the number of symptoms and length of return to play indicated that 2-hydroxybutyrate and lactose may have potential applications as biomarkers for sports related concussion.